2016
DOI: 10.3390/polym8110389
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Alkyl and Aryl Substituents on Iminopyridine Fe(II)- and Co(II)-Catalyzed Isoprene Polymerization

Abstract: Abstract:A series of alkyl-and aryl-substituted iminopyridine Fe(II) complexes 1a-7a and Co(II) complexes 2b, 3b, 5b, and 6b were synthesized. The activator effect, influence of temperature, and, particularly, the alkyl and aryl substituents' effect on catalytic activity, polymer molecular weight, and regio-/stereoselectivity were investigated when these complexes were applied in isoprene polymerization. All of the Fe(II) complexes afforded polyisoprene with high molecular weight and moderate cis-1,4 selectivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(37 citation statements)
references
References 59 publications
1
35
0
1
Order By: Relevance
“…For example, the Co1‐N1 imino bond length (2.073(4) Å) is longer than reported complexes [ranging from 2.0444(19) to 2.0560 (18) Å], suggesting slightly weaker interaction between metal center and N imine . However, the Co1‐N2 imidazole bond length (2.027(4) Å) is found slightly shorter than Chen's complex [(Co1‐N1(pyridyl): 2.040(3) Å], which might be due to the stronger positive electronic effect of N iminoimidazole atom as compared to the N iminopyridine atom and thereby increases the interaction between N and Co center.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…For example, the Co1‐N1 imino bond length (2.073(4) Å) is longer than reported complexes [ranging from 2.0444(19) to 2.0560 (18) Å], suggesting slightly weaker interaction between metal center and N imine . However, the Co1‐N2 imidazole bond length (2.027(4) Å) is found slightly shorter than Chen's complex [(Co1‐N1(pyridyl): 2.040(3) Å], which might be due to the stronger positive electronic effect of N iminoimidazole atom as compared to the N iminopyridine atom and thereby increases the interaction between N and Co center.…”
Section: Resultsmentioning
confidence: 69%
“…= 98.95°). The Cl1‐Co1‐Cl2 [114.42(6)°] and N1‐Co1‐N2 [82.54(14)°] bond angles are found slightly bigger than the corresponding angles reported cobalt complexes [Cl1‐Co1‐Cl2 111.67(4)°–114.55(3)°, N1‐Co1‐N2 79.34(10)°–81.61(13)°] . Meanwhile, the Co‐Cl bond lengths are identical (Co1‐Cl1: 2.2236(14) Å; Co1‐Cl2: 2.2225(14) Å) but slightly longer than previously reported complexes [2.2037(10)–2.2199(8) Å].…”
Section: Resultsmentioning
confidence: 95%
“…Metal‐catalyzed selective isoprene polymerization has been a major entry toward cis ‐1,4, trans ‐1,4, and 3,4 isomers (Scheme ). Ziegler‐Natta type of titanium and neodymium, metallocenes (Cp: cyclopentadienyl and its derivatives) type of titanium and rare earth metal catalysts, non‐Cp ligated lanthanide alkylaluminates, multi‐dentated PNP, or NCN ligand chelated rare earth metal complexes, and cobalt complexes supported by multi‐dentate ligand have been extensively explored for cis ‐1,4 polymerization. The resultant polymer could be a promising alternative to natural rubber for tire industry.…”
Section: Introductionmentioning
confidence: 99%
“…In view of these findings, the authors proposed that higher electron density at the iron center favor trans -1,4 selectivity. Later, Chen et al [28] reported Fe(II) and Co(II) complexes bearing bulky substituents. The complexes containing N-aryl imine groups produced polymer in a higher yield than N-alkyl imine groups, which potentially suggests that electron-withdrawing substituents lead to better monomer coordination and faster chain propagation.…”
Section: Introductionmentioning
confidence: 99%